Respostas

2014-07-22T13:34:03-03:00
Resolvendo:       condiçao--->  cotgx=-2

y= senx+cosecx/cosx-secx
     por propriedade------------> senx=1/cosecx  ;  cosx= 1/secx
     faznedo:
   1/cosecx+cosecx/ 1/secx-secx
    
   1+cosec²x/cosecx
 <-----------------------> ;   cosec²x= 1+ctg²x   e sec²x= 1+tg²x
      1-sec²x/secx 
 
     substituindo:        1+1+ctg²x/cosecx      2+(-2)²/cosecx           6/cosecx
                                 <------------------->=   <----------------->= <----------------->
                                    1-1+tg²x/secx                tg²x/secx                tg²x/secx

multiplicamos meios e extremos:
  
6.secx/cosecx.tg²x  ...............tg²x= 1/ctg²x....ctg²x= (-2)²= 4 ; tg²x= 1/4.
 substituindo.
 
6.secx/ cosecx.1/4=  24secx/cosecx.........secx= 1/cosx  e cosecx=1/senx
 substituindo temos:
 
 24.senx/cosx..................e senx/cosx =tgx =1/ctgx
 
 24/ctgx............ctgx=-2
 
 24/-2=-12.
  y=-12  espero ter ajudado.






1 5 1